Etarã, eg mré ke: parentes - Silva, Bruno Müller da [UNESP] (2017)
Etarã, Ẽg Mré Ke: Parentes is a project inspired by the Guarani and Kaingang native cultures from Brazil. The work is split on three axes: first, the creation of 8 illustrative panels based on elements from the two indigenous cultures. Second, art directing six alumni from the Design undergraduate course in Unesp - Univ. Estadual Paulista, whose illustrations represent myths from both Guarani and Kaingang origin. Lastly, the exhibit organization project, also inspired by cultural concepts, planned to open at the Museu Municipal de Jahu, in Jaú, São Paulo, Brazil, by invitation from the institution